2016
DOI: 10.1093/scan/nsw162
|View full text |Cite
|
Sign up to set email alerts
|

Independent effects of motivation and spatial attention in the human visual cortex

Abstract: Motivation and attention constitute major determinants of human perception and action. Nonetheless, it remains a matter of debate whether motivation effects on the visual cortex depend on the spatial attention system, or rely on independent pathways. This study investigated the impact of motivation and spatial attention on the activity of the human primary and extrastriate visual cortex by employing a factorial manipulation of the two factors in a cued pattern discrimination task. During stimulus presentation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 76 publications
(110 reference statements)
2
28
1
Order By: Relevance
“…Not much is known, however, about the temporal unfolding of neural activity underlying social (versus nonsocial) information processing, and it remains largely unresolved how social content may interact with other stimulus dimensions during stimulus processing, particularly with emotional content in terms of intrinsic pleasantness / hedonic valence. Here, we extend previous EEG data (Bayer et al, 2017;Okruszek et al, 2016) by showing that social content impacts very early stages of stimulus processing, reflected in modulations of the P1 and subsequent ERP components of short latencies. Social content therefore likely represents a unique stimulus dimension that is appraised during one of the first of a series of relevance checks.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Not much is known, however, about the temporal unfolding of neural activity underlying social (versus nonsocial) information processing, and it remains largely unresolved how social content may interact with other stimulus dimensions during stimulus processing, particularly with emotional content in terms of intrinsic pleasantness / hedonic valence. Here, we extend previous EEG data (Bayer et al, 2017;Okruszek et al, 2016) by showing that social content impacts very early stages of stimulus processing, reflected in modulations of the P1 and subsequent ERP components of short latencies. Social content therefore likely represents a unique stimulus dimension that is appraised during one of the first of a series of relevance checks.…”
Section: Discussionsupporting
confidence: 86%
“…Such early social relevance effect in terms of a social versus nonsocial activation difference during complex visual scene processing is corroborated by a recent study using negative versus neutral written sentences as stimuli, and manipulating the social content dimension by means of social closeness (i.e. whether the sen-tences referred to participants' significant others or to unknown agents) (Bayer et al, 2017). The authors also report early social content effects in ERPs in the P1 component (from 73 to 120 ms), and this again irrespective of the sentences' valence.…”
Section: Introductionmentioning
confidence: 60%
See 2 more Smart Citations
“…In the domain of visuospatial attention, the majority of human studies have found no evidence for the notion that attention can modulate the first feedforward sweep of activation, as reflected in the amplitude of the earliest event-related potential (ERP), the C1 (Baumgartner, Graulty, Hillyard, & Pitts, 2018;Bayer et al, 2017;Di Russo et al, 2012;Di Russo, Martinez, & Hillyard, 2003;Martinez et al, 2001;Martínez et al, 1999;Noesselt et al, 2002). This component peaks before 100ms and flips in polarity dependent on whether the stimulus is presented in the upper or lower visual field, suggesting strong contributions of V1 generators (Di Russo et al, 2003;Kelly, Vanegas, Schroeder, & Lalor, 2013).…”
Section: Introductionmentioning
confidence: 99%